Noticing how our social networks are interconnected can influence language change. Issue 1 (15th January 2021) - Lev-Ari, Shiri; Haidari, Bahara; Sayer, Tathra; Au, Vanessa; Nazihah, Fahima
ABSTRACT: Languages constantly change. This requires variants that are initially rare to become dominant. A prime question is how such changes come about. Here we propose that the inter-connectivity of people's contacts, and people's failure to take it into account leads them to over-weigh the informativity of repeated information. In Experiment 1 we find that people do not sufficiently account for the independence of their sources, and that this neglect is stronger for linguistic terms than it is for opinions. In Experiment 2 we conduct simulations on real world networks and find that failure to account for source dependence promotes the spread of innovations. Together, these results show that language and opinions do not follow the same trajectory of change, and that the spread of innovations, and especially linguistic innovations, is facilitated by biases in the way we process information and community structure.